The Relationship Between Self-Perception and Alexithymia with Mental Health Status in Housewives: The Mediating Role of Co-dependency - Mahnaz Einollahzade; alireza kakavand; somayeh keshavarz (مطالعات روانشناختی)
This study aimed to investigate the relationship between self-perception and emotional dyslexia (alexithymia) and the mental health status of housewives, with a focus on the mediating role of co-dependency. Employing a correlation research design and structural equation modelling (SEM), the research sampled 250 housewives who attended five health centres in Tehran province. Data were collected using the Goldberg Mental Health Questionnaire, the Toronto Alexithymia Scale, the Span and Fisher Co-dependency Questionnaire, and the Beck Self-Concept Test. The results showed that the research model had a good fit. According to the results indicated an inverse and significant relationship between emotional dyslexia and co-dependency with mental health among housewives and there was a positive and significant relationship between self-perception and mental health. Furthermore, the mediating role of co-dependency in the relationship between self-perception and mental health status of housewives was confirmed. However, the mediating role of co-dependency in the relationship between emotional dyslexia and mental health status was not supported. According to the results, special attention can be paid to the role of self-perception, alexithymia and co-dependency variables in increasing the mental health of housewives.